(untitled) (British Journal of Multidisciplinary and Advanced Studies, 2023)
The quality of governance depends largely on the role of government institutions through their regulatory and policy making functions; as it empowers private sector driven growth and macro managed domestic currency value. The study focused on Foreign Exchange Management and Economic Growth Nexus: the Role of Institutional Quality in Nigeria. Method of Fully Modified Ordinary Least Squares (FMOLS) was used to study the effect of Institutional quality to Nominal effective exchange rate on Economic growth from 1996 to 2021.Institutional quality functioned as the moderator. The finding showed a significant but inverse relationship between nominal effective exchange rate and economic growth due to decline in institutional quality. Also, the coefficient of interactive term suggests a complimentary effect exist between nominal effective exchange rate and institutional quality in building strong economy. Recommended that, regulatory authorities should work in synergy to develop strategies to regulate and encourage private sector participation in economic growth.